The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.5114/pg.2017.72106
|View full text |Cite
|
Sign up to set email alerts
|

Position change during colonoscopy improves caecal intubation rate, mucosal visibility, and adenoma detection in patients with suboptimal caecal preparation

Abstract: IntroductionMost colonoscopies are completed in the left lateral (LL) position but in cases of suboptimal caecal preparation, changing the patient’s position to supine (S) and, if needed, to right lateral (RL) improves caecal intubation rate, mucosal visibility, and adenoma detection.AimTo determine if position change during colonoscopy facilitates optimal visualisation of the caecum.Material and methodsA total of 359 patients were grouped into three categories based on the initial caecal intubation position. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…When compared to the other two styles, the relatively high number of maneuvers to correct/reposition the endoscope, the number of patient position changes during the procedure, and post-procedure endoscopist fatigue support this argument. Various studies have shown that changing the patient's position during the procedure contributes positively to ADR [17][18][19]. Undoubtedly, all these maneuvers would lead to extra operator fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the other two styles, the relatively high number of maneuvers to correct/reposition the endoscope, the number of patient position changes during the procedure, and post-procedure endoscopist fatigue support this argument. Various studies have shown that changing the patient's position during the procedure contributes positively to ADR [17][18][19]. Undoubtedly, all these maneuvers would lead to extra operator fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the reason for incomplete cecal intubation may help guide the particular approach in subsequent attempts (36). There are also patient factors that may hinder the ability to reach the cecum, including low body mass index, history of hysterectomy, bowel preparation quality, anatomy, inflammation, and obstruction (37)(38)(39)(40)(41). Withdrawal time: WT, the time measured from when the colonoscope reaches the cecum to the time the scope is withdrawn from the anus in the absence of polyp removal, has also been studied as a quality metric in colonoscopy.…”
Section: $10%mentioning
confidence: 99%
“…This is best performed under water immersion, with the use of a distal attachment/cap and by rolling the patient out of the left lateral decubitus position (in most patients, the cecum is best examined with the patient in the right lateral decubitus position). 7…”
Section: Endoscopic Approach and Evaluationmentioning
confidence: 99%